2004
DOI: 10.1021/jp040140l
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Energy Transfer between Hot Pyrazine and Cold CO:  A Classical Trajectory Study

Abstract: Vibrational energy transfer from hot pyrazine (E′ ) 40 322 cm -1 ) to cold CO is modeled using classical trajectories. Collisional energy transfer properties are studied as a function of the initial rotational state J′ of the CO, the length of the CO, the energy E′ in pyrazine, the relative kinetic energy, the temperature, isotopic substitution on pyrazine, and the intermolecular potential. The energy transfer probability function P(E,E′) exhibits distinct deviation from single exponential behavior. Collisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…[44][45][46][47][48][49][50] In addition to the first and second moments of P͑E , EЈ͒ it is possible to obtain mechanistic information on the energy transfer process [48][49][50] and even qualitative information on the shape of P͑E , EЈ͒, including the supercollision tail. Classical trajectory calculations were used to calculate collisional energy transfer quantities mainly in polyatomicmonatomic collisions but also in polyatomic-polyatomic collisions.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47][48][49][50] In addition to the first and second moments of P͑E , EЈ͒ it is possible to obtain mechanistic information on the energy transfer process [48][49][50] and even qualitative information on the shape of P͑E , EЈ͒, including the supercollision tail. Classical trajectory calculations were used to calculate collisional energy transfer quantities mainly in polyatomicmonatomic collisions but also in polyatomic-polyatomic collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman and co-workers used quasiclassical trajectory calculations to investigate the energy transfer of highly vibrationally excited pyrazine in collisions with CO at 300 K [116]. They showed that most collisions, typically about 80%, are direct, exhibiting only one turning point in the relative coordinate.…”
Section: Role Of Collisional Complexesmentioning
confidence: 99%
“…In the study of energy transfer between pyrazine and CO, Chapman and co-workers also investigated the effects of initial translational energy [116]. They showed that the average energy transfer for energy-up collisions increases as the translational energy increases, but average energy-down collisions does not change.…”
Section: Effects Of Initial Translational Energymentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23][24][25][26] The calculation indicates how the energy transferred per collision depends on the internal energy of polyatomic molecules, on the intermolecular potential, on the mass of the bath, on the duration of collision, on the minimal distance of approach, on the relative velocity, on the vibrational modes, and on the rotation of polyatomic molecules. [14][15][16][17][18][19][20][21][22][23][24][25][26] The calculation indicates how the energy transferred per collision depends on the internal energy of polyatomic molecules, on the intermolecular potential, on the mass of the bath, on the duration of collision, on the minimal distance of approach, on the relative velocity, on the vibrational modes, and on the rotation of polyatomic molecules.…”
Section: Introductionmentioning
confidence: 99%